Suppression of Lipopolysaccharide‐Induced Sepsis by Tetrahedral Framework Nucleic Acid Loaded with Quercetin. (15th August 2022) - Liu, Zhiqiang; Chen, Xingyu; Ma, Wenjuan; Gao, Yang; Yao, Yangxue; Li, Jiajie; Zhang, Tianxu; Qin, Xin; Ge, Yichen; Jiang, Yueying; Lin, Yunfeng
Abstract: Sepsis has affected millions of people worldwide with high mortality rate and lack of effective strategies. Previous studies have reported that quercetin (Que) can attenuate lipopolysaccharide (LPS)‐Induced sepsis. However, for poor water solubility, low bioavailability, and instability, the application of Que is limited. Hence, a nano‐system is constructed to deliver Que based on tetrahedral framework nucleic acid (tFNA), namely tFNA‐Que. For the anti‐inflammatory, anti‐oxidant, and delivery performance of tFNA, tFNA is designed as the effective carrier to deliver Que. The tFNA‐Que possesses the simple synthesis method, stable performance, good biocompatibility, favorable water solubility, excellent anti‐inflammatory, and anti‐oxidation property. As a result, tFNA‐Que can attenuate LPS‐Induced systemic inflammation and multiple organ injury of mice. In brief, the synthesis of tFNA‐Que provides a simple and effective synergistic delivery nano‐system, which may be a promising candidate for sepsis. Abstract : The tFNA‐Que possesses a simple synthesis method, sustained release, stable performance, good water solubility, and excellent biocompatibility. The tFNA‐Que can improve the anti‐inflammatory effect via ERK/NF‐κB pathway and enhance the antioxidant capacity via Nrf2/HO‐1 pathway. The tFNA‐Que can reduce systemic inflammation and protect multiple organs containing lung, liver, and kidney from injuries of sepsis by regulating macrophages.